2000
DOI: 10.1097/00002341-200007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus After Balanced Medial Plus Lateral Wall Versus Lateral Wall Only Orbital Decompression for Dysthyroid Orbitopathy

Abstract: Lateral wall orbital decompression may produce less new-onset, persistent postoperative strabismus than balanced medial plus lateral wall orbital decompression for dysthyroid orbitopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
2
24

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(151 citation statements)
references
References 11 publications
6
119
2
24
Order By: Relevance
“…22 In 16 studies on transconjunctival, transcaruncular, and translid decompression, the reported incidence of NOD ranged from 0 25 to 33%. 31 In one of these studies, 28 the reported incidence of NOD was 9% vs a recalculated value of 25%. In five other studies, a combined transnasal and translid/transconjunctival approach was used, with a reported incidence of NOD ranging from 0 34,35 to 12%.…”
Section: Other Side Effects and Complicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…22 In 16 studies on transconjunctival, transcaruncular, and translid decompression, the reported incidence of NOD ranged from 0 25 to 33%. 31 In one of these studies, 28 the reported incidence of NOD was 9% vs a recalculated value of 25%. In five other studies, a combined transnasal and translid/transconjunctival approach was used, with a reported incidence of NOD ranging from 0 34,35 to 12%.…”
Section: Other Side Effects and Complicationsmentioning
confidence: 99%
“…18 Recalculation of data from studies on anterior approach three-wall orbital decompression, including translid, transconjunctival ('swinging eyelid'), and coronal techniques show relatively low NOD frequencies of 0 to 33% (Table 6). Although it was speculated that a 'balancing effect' of lateral and medial wall decompression may limit the frequency of NOD, 7,24,26,31,35,38 recent studies 25,30 failed to show a difference between translid or transconjunctival two-wall decompression and coronal three-wall decompression in that respect.…”
Section: Eyementioning
confidence: 99%
See 3 more Smart Citations